GEOLOGI DAN KARAKTERISTIK ENDAPAN BIJIH MANGAN DI DAERAH CILEUTAK, KECAMATAN SIMPENAN, KABUPATEN SUKABUMI, PROVINSI JAWA BARAT - , IRENA SULISTYA A. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Manganese is exposed in the area Cileutak, Simpenan subdistrict , Sukabumi District , West Java Province is found only local. Outcrops of manganese is found in the form of fracture filling, as matriks rocks and manganese in rock fragments. The manganese outcrops associated with volcanic rocks consisting of andesite to basaltic andesite host rock, where the rock becomes a source of enrichment of manganese in the study area. In carriers of the host rock geochemistry of manganese deposition is derived from the magma series calc - alkaline affinity associated with subduction zones in island arc. Manganese deposit in the study area are composed of mineral manganite (MnO(OH)) and mineral rodocrosite (MnCO3) as the primary mineral minerals while pirolusite (MnO2) as a mineral formed by oxidation and decomposition of minerals rodokrosite and manganite. Propylitic alteration is a alteration in the study area. This alteration type is characterized by the presence of chlorite and epidote minerals, which indicates the type of hydrothermal deposition of the mineral formation temperatures ranging from 200oC - 300oC which is an epithermal type deposit. From the comparison of Mn and Fe elements that exist in both types of deposits can be demonstrated that manganese is formed in the study area is derived from hydrothermal processes associated with subduction zones in the island arc. Deposit manganese model in the study area were made by local geological conditions using data manganese ore mineralogy and geochemistry. The model explains that the manganese sediment control structures such as cracks and faults existing in the study area to help process the manganese enrichment in the area of research with processes such as leaching and dissolution of Mn elements that exist in the host rock by hydrothermal fluids and meteoric fluids.